Effect of Acupressure at ST 36 & SP 6 Points on Hemoglobin Levels among Adolescent Girls: Preliminary Study - Nyna Puspita Ningrum; Setiawandari Setiawandari (EMBRIO: Jurnal Kebidanan, 2022)
Menstruation is one of signs of puberty in adolescent girls. The process of menstruation often affects hemoglobin levels in adolescent girls regarding the incidence of anemia and may also have a negative effect on the growth and development of adolescent girls. In addition to the iron tablet supplementation program, several non-pharmacological methods can be applied as an alternative to increase hemoglobin levels among adolescent girls with anemia, one of which is acupuncture and acupressure methods. This was a pre-experimental study with a one group pretest posttest design. The population involved 25 adolescent girls at Taruna Pembangunan Intensive High School in Surabaya according to the inclusion criteria. In further stage, the samples were trained how to perform acupressure at Zusanli (ST36) point and Sanyinjiao (SP 6) point every 2 days for 10 minutes which was carried out for 2 months from September to November 2021. Data that had been collected were tested for homogeneity and analyzed by Wilcoxon test. Before acupressure, almost half of the respondents had Hb levels of 11-12 mmHg (44%), and 7 respondents had Hb levels of <11 mmHg. After acupressure therapy, more than half of the respondents had Hb levels of 13-14 mmHg (53%). The Wilcoxon signed rank test obtained a p value = 0.000 (<0.05) which meant that there was a difference between Hb levels in pre-test and post-test. Thus, it can be concluded that there was an effect of acupressure at ST36 and SP 6 points on the increase in hemoglobin levels among adolescent girls. However, there is a need for further research on acupressure method which involved more samples and subjects with different levels of anemia, so as to confirm the effectiveness of acupressure on the increase in hemoglobin levels.